THE DYNAMICS OF ORGANIZATIONAL CAPABILITIES AND THEIR IMPLICATIONS FOR INTERNAL SERVICE QUALITY IN PUBLIC INSTITUTIONS: A STUDY OF THE REGIONAL OFFICE AND IMMIGRATION UNITS IN WEST KALIMANTAN - M Arief Wibowo; Anang Kistyanto; Dewie Tri Wijayati Wardoyo (Universitas Nusa Cendana, 2026)
This study aims to analyze the influence of Digital Transformation and Human Resource Management Practices on Internal Service Quality, with Organizational Agility as a mediating variable at the Regional Office of the Directorate General of Immigration in West Kalimantan. The research employs a quantitative survey method using proportionate stratified sampling, involving 254 employees as respondents. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Digital Transformation and Human Resource Management Practices have a significant effect on improving Internal Service Quality, both directly and indirectly through the enhancement of Organizational Agility. Organizational Agility also plays a mediating role in strengthening the relationship between these variables, highlighting its importance as a dynamic capability within the organization. The study concludes that strengthening digital integration, implementing adaptive human resource management practices, and improving organizational responsiveness are essential for enhancing internal service quality in public sector institutions. From a theoretical perspective, this research contributes to the development of the Resource-Based View and Social Exchange Theory within the context of digital public services. However, this study is limited by its cross-sectional research design, and future studies are recommended to use longitudinal approaches to better understand the causal relationships among the variables. Keywords: Digital Transformation; Human Resource Management Practices ; Organizational Agility; Internal Service Quality; Public Sector; Immigration Office